Análise de uma interseção rodoviária por meio de simulação de tráfego: estudo de caso da interseção Tancredo Neves x Sete de Setembro em Tucuruí-PA - SILVA, Romerson Serejo (2022)
This work presents an analysis of a highway intersection located in the city of Tucuruí (State of Pará) using computational simulation. The simulation was made by the Synchro Studio software’s package, which simulate road traffic through macrosimulation and microsimulation. The simulations had as objective collect important Traffic Engineering data of the intersection in its current conditions, as well as its behavior in alternative scenarios with vehicle volumetric projections and then presenting software’s optimized scenarios, and possible measures to mitigate problems encountered in the simulated intercession. Seven different scenarios for intersection were simulated using traffic volume data countered in the field and vehicle volumetric projections for 5 (five), 10 and 15 years in the future, and using different signal controls as well. The data presented in the result section shows mainly the values from the intersection’s Level-of-Service (LOS) and the average control delays for the non-optimized scenarios. The optimized scenarios had as results the splits and phases from the traffic control signals in addition. In the simulation results the intersection presented the level-of-service D for its current conditions, which is a level-of-service indicating the intersection is starting to have problems. The intersection reaches the LOS F in scenarios 4 and 5, with volumetric projections for 10 and 15 years. The level F indicates high and bad congestion at intersection. The average delays results had shown high peaks on volumetric projection scenarios, reaching an extreme delay of 389.9 seconds in 15 years` projection from scenario 4. As a mitigation for possible future problems, the work presented some optimization scenarios made by the software as well as a scenario that forbids the left turns on the intersection north and south approaches, providing improvements in the level-of-service and mitigating the intersection problems in these scenarios.